2021
DOI: 10.1002/ski2.73
|View full text |Cite
|
Sign up to set email alerts
|

Stigma, social appearance anxiety and coping in men and women living with skin conditions: A mixed methods analysis

Abstract: Background:The psychological impact of living with a skin condition can have a profound impact on quality of life and could cause appearancerelated social anxiety. Existing research suggests ambiguous findings in relation to whether the impact of living with a skin condition differs between males and females. Objectives: The present study aimed to explore the association between stigma, coping styles and social appearance anxiety in men and women living with a skin condition in the United Kingdom. Methods: 231… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
28
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 49 publications
0
28
1
Order By: Relevance
“…However, this study could not establish an association between psychotherapy and psychosocial problems of Vitiligo. The findings of the study are not consistent with the previous studies where psychotherapy has been found to play a moderator role in the regulation of self-esteem, depression, and improvement of quality of life among patients with diseases involving disfigurement and altered body appearance (10,15). As in this study those who received psychotherpy showed no significant change in their quality of life and reduction in effects of Vitiligo.…”
Section: Discussioncontrasting
confidence: 99%
“…However, this study could not establish an association between psychotherapy and psychosocial problems of Vitiligo. The findings of the study are not consistent with the previous studies where psychotherapy has been found to play a moderator role in the regulation of self-esteem, depression, and improvement of quality of life among patients with diseases involving disfigurement and altered body appearance (10,15). As in this study those who received psychotherpy showed no significant change in their quality of life and reduction in effects of Vitiligo.…”
Section: Discussioncontrasting
confidence: 99%
“…14 This might explain why skin conditions have been associated with depression, [14][15][16][17] low self-esteem and maladaptive self-beliefs or appearance anxiety. [18][19][20] In an attempt to avoid negative evaluations and humiliation, people with psoriasis may anticipate rejection, withdraw socially 21 or experience shame. 13,22 Anger has been reported in people with skin conditions 23 including alopecia, 4 urticaria 24 and psoriasis 4,25,26 from their uncontrollable nature, or as an outcome of poor mental health.…”
Section: Introductionmentioning
confidence: 99%
“…It includes equally Psychiatric diseases that present with skin symptoms and signs (such as delusional infestation) or more commonly, the psychiatric or psychological problems associated with dermatological illness, such as depression associated with psoriasis. 4 Since the journal was launched, I noticed that we had had quite a few manuscripts submitted that would definitely fit under the category of predominantly Psychodermatology or Dermatology manuscripts with a psychological overlay. 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 The editorial team of SHD will launch a themed issue later in the year on the subject of Psychodermatology.…”
mentioning
confidence: 99%
“… 4 Since the journal was launched, I noticed that we had had quite a few manuscripts submitted that would definitely fit under the category of predominantly Psychodermatology or Dermatology manuscripts with a psychological overlay. 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 The editorial team of SHD will launch a themed issue later in the year on the subject of Psychodermatology. I am extremely grateful to Prof Tony Bewley and Dr Susannah Baron (London) and Prof John Koo and Dr Marwa Hakimi (San Francisco) for agreeing to be guest editors.…”
mentioning
confidence: 99%
See 1 more Smart Citation